2012
DOI: 10.1097/igc.0b013e318249bf02
|View full text |Cite
|
Sign up to set email alerts
|

Better Anatomical and Cosmetic Results Using Tunneled Lotus Petal Flap for Plastic Reconstruction After Demolitive Surgery for Vulvar Malignancy

Abstract: Tunneled lotus petal flap is safe, easy and fast to perform, has a low rate of complications, and good functional and cosmetic results. This technique represents an optimal solution for plastic reconstruction in case of primary or recurrent vulvar disease, or in case of introital stenosis after primary inadequate closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Yii et al [14] were the first in 1996 to report on reconstruction using the LP flap. All but three of these studies are case series [14][15][16][17][18][19][20][21][22][23][24][25][26]. Only Negosanti et al [27], Confalonieri et al [18] and Thiele et al [28] reported a case control study in which a reconstruction with LP flaps was compared with other flaps.…”
Section: Lp Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yii et al [14] were the first in 1996 to report on reconstruction using the LP flap. All but three of these studies are case series [14][15][16][17][18][19][20][21][22][23][24][25][26]. Only Negosanti et al [27], Confalonieri et al [18] and Thiele et al [28] reported a case control study in which a reconstruction with LP flaps was compared with other flaps.…”
Section: Lp Reconstructionmentioning
confidence: 99%
“…About half of the studies (56.3%) were small studies (<20 patients), the largest was that of Confalonieri et al which included 106 patients [14,18,[20][21][22]24,[26][27][28]. In 62.5% of the studies, only females were included [14,15,[17][18][19]21,23,[25][26][27]. Mean age of the subjects varied between 50.3 years and 79 years [21,22].…”
Section: Lp Reconstructionmentioning
confidence: 99%
“…3,4 From 2007, we identified LPF as the most appropriate method of reconstruction after vulvoperineal surgery for both primary and recurrence vulvar malignancy.…”
mentioning
confidence: 99%
“…In addition, the incidence of complications remains low even when we added the series of 22 women who underwent reconstructive surgery using modified tunneled LPF. 4 When all the 63 operated patients are considered, wound complications occurred only in 9.5% of cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation